NATURAL OCCURRENCE OF FOUR REVERSIBLE FLAGELLAR PHASES IN CULTURES OF SALMONELLA MIKAWASHIMA - Edwards, P. R. (1962)
Edwards, P. R. (Communicable Disease Center, U.S. Public Health Service, Atlanta, Ga.), R. Sakazaki, and I. Kato. Natural occurrence of four reversible flagellar phases in cultures of Salmonella mikawashima. J. Bacteriol. 84:99–103. 1962—Study of cultures of Salmonella mikawashima isolated from reptiles revealed that single colonies of some strains contained three distinct H phases and that colonies of other cultures contained four such phases. In addition to the usual y and e,n,z(15) phases of S. mikawashima, two additional antigens which occurred naturally and which were identical with naturally occurring H antigens of the Arizona group, designated z(47) and z(50), were recognized. Some cultures were represented by the formula 6,7:y:-e,n,z(15):z(47), some by 6,7:y:e,n,z(15):z(50), and some by 6,7:y:e,n,z(15):z(47):z(50). The four H antigens were serologically unrelated, and each could be caused to revert to the others. Spontaneous reversions also were observed. The organisms underwent loss variation, and stable diphasic forms were encountered in which the e,n,z(15) phase occurred in conjunction with y, z(47), or z(50), indicating that the three antigens may be alternative forms of phase 1.